Math, asked by nemoimran23, 6 months ago

factorize x¹² - y¹² = ??​

Answers

Answered by saanvigrover2007
1

 \sf{ \looparrowright Identity \: used \:  =  {x}^{2} -  {y}^{2}  = (x + y)(x - y) } \\  \:

 \sf{ \looparrowright \: Solution : }

 \sf{ {x}^{12}  -  {y}^{12} = ( {x}^{6})^{2} - ( {y}^{6})^{2} } \\  \sf{ =( {x}^{6}  -  {y}^{6} )( {x}^{6}   +  {y}^{6} )  } \\   \sf \blue{ = (x - y)( {x}^{2}  + xy +  {y}^{2})( {x}^{3}   +  {y}^{3})( {x}^{6}  +  {y}^{6} ) }

 \texttt{Refer to attachment for full solution}

Attachments:
Similar questions